Sustainability Analysis on Economic and Ecological Aspects of Dry Land Management in Jerowaru District Using Multi Dimensional Scaling (MDS) - Jasmawadi, Lalu Agus; Budastra, I Ketut; Tajidan, Tajidan; Zaini, Anas; Siddik, Muhamad (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
This study aims to determine the factors from the ecological and economic aspects that have the most sensitive attributes in influencing the sustainability of dry land management in Jerowaru District. This study uses the Multi Dimensional Â Scaling (MDS) analysis of Rapfish. The population in this study were all dry land farmers in Jerowaru District, East Lombok. The number of farmer respondents surveyed was 90 farmers spread over three villages with varied agricultural cropping patterns and topography. The sample unit in this study were individuals, namely dry land farmers. The sample in this research is some farmers who do dry land management. The analysis used is descriptive and MDS Rapfish is supported by qualitative analysis from field observations and in-depth interviews as outlined in a descriptive analysis to determine the characteristics of each respondent while MDS Rapfish is used to determine the most sensitive factors on ecological and economic aspects. The results of the feasibility study were tested with the r2 value which is close to one and the stress value <20% and the results of the Monte Carlo analysis which have a difference of <5% with the MDS results. The results of the MDS analysis show that the sustainability status on the economic aspect is 46.3 and on the ecological aspect it is 39.08. On the economic and ecological aspects in the less sustainable category. Leveraging factors from leveraging analysis to improve the status of sustainability in the economic aspect are the availability of inputs, especially fertilizers, access to marketing and availability of water for farming. While the lever factors in the ecological aspect are the use of biochar, the occurrence of floods / landslides, and vegetation cover. These levers must be a priority for sustainable dryland agricultural management in Jerowaru District, East Lombok.